Inovasi Dalam Dakwah: Memanfaatkan Teknologi Untuk Menyebarkan Pesan Islam Secara Efektif - Aulia, Hanna (Gayaku Publisher, 2025)
This research examines innovations in da'wah by utilizing technology to effectively disseminate Islamic messages, based on a narrative review of 30 articles indexed in Sinta 3. In the current digital era, advancements in information and communication technology have opened new opportunities for the dissemination of da'wah through social media, mobile applications, and other online platforms. The findings indicate that the use of technology not only expands the audience reach but also enhances interaction and engagement with da'wah content. Various methods, such as multimedia content creation and the application of digital marketing strategies, have proven effective in capturing the attention of younger generations. However, challenges such as the spread of inaccurate information and resistance to change must be addressed with a thoughtful approach. This study emphasizes the importance of adapting da'wah to technological advancements to ensure that Islamic messages are well received and understood by diverse segments of society.